ADOPSI TEKNOLOGI SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SLPTT) PETANI PADI SAWAH DI DESA SUTOJAYAN KECAMATAN PAKISAJI KABUPATEN MALANG - Wea, Paulinus; Mutiara, Farah; Masduki, Said (Universitas Tribhuwana Tunggadewi, 2019)
Adoption of Technology of Integrated Crop Management Field School (SL-PTT) of paddy rice farmers in Sutojayan Village, Pakisaji District, Malang Regency, is one component in the government program to increase farmers' knowledge and skills in adopting the technology of lowland rice crops. This study aims to 1) examine the form of technology in SL PTT rice paddy farmers, members of farmer groups. 2) analyzing the adoption of SL PTT technology in paddy rice farmers in members of farmer groups in Sutojayan Village, Pakisaji District, Malang Regency. The data used in this study are primary and secondary data. Methods of data collection using observation, interviews, documentation and questionnaires, data analysis techniques using qualitative data analysis using interative models. The results of this study indicate that the SLPTT technology applied in the village of Sutojayan is divided into several components, namely the main components consisting of the use of rice paddy seed varieties, fertilization, planting systems, integrated pest control and supporting components consisting of tillage, planting young seedlings, intermittent, weeding and post-harvest irrigation, as well as from the analysis of SLPTT technology adoption of farmers in Sutojoyan Village, can be seen from the form of applied technology adoption, where the adoption activities applied are well received by farmers. Adopsi Teknologi Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) petani padi sawah di Desa Sutojayan Kecamatan Pakisaji Kabupaten Malang, merupakan salah satu komponen dalam program pemerintah untuk meningkatkan pengetahuan dan keterampilan petani dalam mengadopsi teknologi tanaman padi sawah. Kajian ini bertujuan untuk 1) mengkaji bentuk teknologi pada SL PTT petani padi sawah anggota kelompok tani. 2) menganalisis adopsi teknologi SL PTT petani padi sawah pada anggota klompok tani di Desa Sutojayan Kecamatan Pakisaji Kabupaten Malang. Data yang digunakan dalam kajian ini adalah data primer dan sekunder. Metode pengumpulan data menggunakan observasi, wawancar, dokumentasi dan kuesioner, teknik analisis data menggunakan analisis data kualtatif dengan menggunakan model interative. Hasil kajian ini menunjukkan bahwa bentuk teknologi SLPTT yang diterapkan di Desa sutojayan terbagi menjadi beberapa komponen yakni komponen utama yang terdiri dari penggunaan varietas benih padi sawah, pemupukan, sistem tanam, pengendalian hama terpadu dan komponen penunjang yang terdiri dari pengolahan tanah, tanam bibit muda, pengairan berselang, penyiangan dan pasca panen, serta dari hasil analisis adopsi teknologi SLPTT petani di Desa Sutojoyan di lihat dari bentuk kegiatan adopsi teknologi yang diterapkan, dimana kegiatan adopsi yang diterapkan diterima baik oleh petani.